2008
DOI: 10.1161/circulationaha.107.730259
|View full text |Cite
|
Sign up to set email alerts
|

Embolic Protection and Platelet Inhibition During Renal Artery Stenting

Abstract: Background-Preservation of renal function is an important objective of renal artery stent procedures. Although atheroembolization can cause renal dysfunction during renal stent procedures, whether adjunctive use of embolic protection devices or glycoprotein IIb/IIIa inhibitors improves renal function is unknown. Methods and Results-One hundred patients undergoing renal artery stenting at 7 centers were randomly assigned to an open-label embolic protection device, Angioguard, or double-blind use of a platelet g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 159 publications
(68 citation statements)
references
References 33 publications
3
65
0
Order By: Relevance
“…Like many other uncontrolled case series, the observation of blood pressure improvement after renal artery stenting in this series should not be interpreted as a successful outcome of the stent procedure, since it could be attributed to regression to the mean or other phenomena associated with clinical trial participation (e.g., Hawthorne effect), since randomized trials have not shown statistically significant differences in blood pressure outcomes between those treated with revascularization and those managed medically(1, 2, 810). In addition, we observed that the use of a distal embolic protection device (DPD) during renal artery stenting had no discernible effect on clinical outcomes (Tables 8a and 8b), which is similar to that reported in a randomized trial of DPD use(11). …”
Section: Discussionsupporting
confidence: 79%
“…Like many other uncontrolled case series, the observation of blood pressure improvement after renal artery stenting in this series should not be interpreted as a successful outcome of the stent procedure, since it could be attributed to regression to the mean or other phenomena associated with clinical trial participation (e.g., Hawthorne effect), since randomized trials have not shown statistically significant differences in blood pressure outcomes between those treated with revascularization and those managed medically(1, 2, 810). In addition, we observed that the use of a distal embolic protection device (DPD) during renal artery stenting had no discernible effect on clinical outcomes (Tables 8a and 8b), which is similar to that reported in a randomized trial of DPD use(11). …”
Section: Discussionsupporting
confidence: 79%
“…17 Kidney function change after stent placement was defined as above in the GuardWire study. After stent placement, there was stabilization or improvement in kidney function in 96% of the patients with significant decrease in systolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…17 The primary end point was absolute change in MDRD derived eGFR and percentage change from baseline to 30 days after renal artery stenting plus abciximab, filter-based embolic protection, or both. The mean eGFRs in these patients ranged from 52 to 66 mL/min prior to the intervention, mostly stages 3A and 2.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Kanjwal et al revealed that, in a prospective study of embolic protection, a surprisingly high rate of platelet-rich thrombi were recovered during renal artery stenting [44]. In a follow-up study, Cooper et al observed that a platelet glycoprotein IIb/IIIa inhibitor, abciximab, was associated with better renal function 1 month after the procedure [45]. Antiplatelet therapy is important in optimal medical therapy of ARVD and is used for all patients with ARVD.…”
Section: Antiplatelet Therapymentioning
confidence: 99%